Analisis Pengelolaan Angkutan Penyeberangan Terhadap Kelancaran dan Keamanan Arus Penumpang dan Barang: Studi Riset pada Sistem Aplikasi Ferizy Pelabuhan Penyeberangan Merak dan Bakauheni - Junaidi; Simanjuntak, Pargaulan Dwikora; Hidayat, Kamarul (Meteor STIP Marunda, 2023)
The main problem in service at the Merak Bakauheni Port is the lack of attention to governance, especially in the application of the ferizy application system to the smoothness and safe flow of passengers and goods. Therefore, this research aims to investigate the impact of implementation of the Ferizy application system in ticket purchases on the smoothness and safe of passengers flow and goods at the Merak-Bakauheni Ferry Port. We use quantitative methods by involving using questionnaires that have been filled by 69 respondents. Furthermore, we use the Method of Succesive Interval (MSI) to convert ordinal scale data into intervals in the utilized questionnaire and conduct inferential testing (multivariate analysis MANOVA) to answer the research hypothesis. The research results indicate that the implementation of the Ferizy application (system quality, information quality, service quality, and user satisfaction) made a significant difference to the smoothness and safe of passengers flow and goods simultaneously and partially. The findings of this study specifically discuss the difference in data results on the ferizy application and the manifest of the Sailing Approval Letter (SPB), from the Merak-Bakauheni port and the Bakauheni-Merak port.